2002
DOI: 10.1007/s10164-002-0064-9
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic signals of a solitary subterranean rodent Ctenomys talarum (Rodentia: Ctenomyidae): physical characteristics and behavioural correlates

Abstract: The purpose of this study was to analyse and describe vocalizations of a solitary subterranean rodent, Ctenomys talarum . In adult C. talarum five different sounds (four true vocalizations and one mechanical sound) were recorded during different behavioural contexts. Using data from the laboratory and literature, we classified these vocalizations as territorial, distress, and mating calls. We found that the vocalization range in C. talarum is shifted towards low frequencies, which transmit better in undergroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 24 publications
0
53
0
1
Order By: Relevance
“…Vocalizations of several species representing five subterranean rodent genera studied so far (Fukomys, Ctenomys, Heterocephalus, Spalacopus, and Spalax) showed tuning to a lower frequency range than that in above-ground rodents (Credner et al 1997;Heth et al 1988;Nevo et al 1987;Pepper et al 1991;Schleich and Busch 2002;Veitl et al 2000). Correspondingly, behavioural audiograms of five species of five subterranean rodent genera (Fukomys, Geomys, Heterocephalus, Spalacopus and Spalax) revealed the highest hearing sensitivity in this lower frequency range (0.5-4 kHz; Begall et al 2004;Brückmann and Burda 1997;Heffner and Heffner 1990, 1993.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Vocalizations of several species representing five subterranean rodent genera studied so far (Fukomys, Ctenomys, Heterocephalus, Spalacopus, and Spalax) showed tuning to a lower frequency range than that in above-ground rodents (Credner et al 1997;Heth et al 1988;Nevo et al 1987;Pepper et al 1991;Schleich and Busch 2002;Veitl et al 2000). Correspondingly, behavioural audiograms of five species of five subterranean rodent genera (Fukomys, Geomys, Heterocephalus, Spalacopus and Spalax) revealed the highest hearing sensitivity in this lower frequency range (0.5-4 kHz; Begall et al 2004;Brückmann and Burda 1997;Heffner and Heffner 1990, 1993.…”
Section: Introductionmentioning
confidence: 93%
“…Compared to a plethora of papers on anatomy and function of the ear (Begall and Burda 2006;Burda et al 1989Burda et al , 1992Kössl et al 1996;Mason 2001;Müller et al 1992;Schleich and Busch 2004;Wilkins et al 1999), hearing (Begall et al 2004;Brückmann and Burda 1997;Heffner and Heffner 1990, 1993Müller and Burda 1989), and vocalizations (Credner et al 1997;Heth et al 1988;Nevo et al 1987;Pepper et al 1991;Schleich and Busch 2002;Veitl et al 2000), however, only one study has dealt with propagation of airborne sounds in burrows (Heth et al 1986). It showed that in a burrow of the blind mole-rat (Spalax ehrenbergi), sounds were only transmitted over short distances (up to 5 m), and signals of 440 Hz were transmitted better than sounds of lower and higher frequencies; these findings correspond to the frequency characteristics of best hearing and vocalizations in the blind mole-rat.…”
Section: Introductionmentioning
confidence: 99%
“…The subterranean ecotope is a relatively stable environment (Nevo 1979) that has influenced the sensory adaptations of its inhabitants (Schleich & Busch 2002;Begall et al 2007). Living in total darkness has resulted in reduced or totally degenerate vision in many subterranean rodents (Nevo 1979).…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of seismic signals, not known to occur in Ctenomys (Francescoli 1999(Francescoli , 2000Schleich and Busch 2002a), acoustic signals are the only source of longrange communication for tuco-tucos (Francescoli 2000) capable of attaining other conspecifics in their burrow systems (Francescoli 1999(Francescoli , 2000(Francescoli , 2002. From all the signals described in tuco-tuco's repertoire, S-type signals (Francescoli 1999) represent the major possibility.…”
mentioning
confidence: 97%